La participación y su viabilidad en Costa Rica - Arguedas Leitón, Enid (2008)
This article is intended to discuss about existent national legislation concerning community and student participation. It is focused on rural communities because of their serious limitations as well as their great potential for development. An education for effective participation of the rural citizens is necessary since their first learning processes, in order to achieve their full and effective insertion inside the national and global market.